(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2024)
Tourism is not only the largest sector in the world economy, but also one of the fastest growing emerging industries in the world. Unlike other economic sectors that transport products to consumers, tourism enables people to migrate to places where tourism resources are concentrated. These resources are consumed somewhere. With the development of social economy, tourism has increasingly shown its important position in the national economy. After years of development, Kazakhstan’s tourism industry has made significant contributions to the national economic development. At the same time, the industry has also accumulated many problems and contradictions in the long-term development process. From a macro level, the development situation of Kazakhstan’s tourism industry is good, with total tourism revenue and tourist numbers rising rapidly. From a micro level, tourism enterprises are small in scale, have poor operations, and have low overall competitiveness. From the industrial level analysis, the main problems and contradictions of Kazakhstan’s tourism industry are related to its market structure characteristics. Structural issues are core issues in the development of tourism in Kazakhstan. Using structural ideas and methods to study the tourism industry in Kazakhstan can guide the sustainable development of the tourism industry and provide a basis for decision-making by the government. Based on the literature review of the tourism market structure, the authors analyze the optimization path based on the Kazakhstan tourism market structure and effectively promotes the tourism industry.